Electric field calculation and peripheral nerve stimulation prediction for head and body gradient coils. Issue 4 (3rd June 2021) - Roemer, Peter B.; Wade, Trevor; Alejski, Andrew; McKenzie, Charles A.; Rutt, Brian K.
Abstract : Purpose: To demonstrate and validate electric field (E‐field) calculation and peripheral nerve stimulation (PNS) prediction methods that are accurate, computationally efficient, and that could be used to inform regulatory standards. Methods: We describe a simplified method for calculating the spatial distribution of induced E‐field over the volume of a body model given a gradient coil vector potential field. The method is easily programmed without finite element or finite difference software, allowing for straightforward and computationally efficient E‐field evaluation. Using these E‐field calculations and a range of body models, population‐weighted PNS thresholds are determined using established methods and compared against published experimental PNS data for two head gradient coils and one body gradient coil. Results: A head‐gradient‐appropriate chronaxie value of 669 µs was determined by meta‐analysis. Prediction errors between our calculated PNS parameters and the corresponding experimentally measured values were ~5% for the body gradient and ~20% for the symmetric head gradient. Our calculated PNS parameters matched experimental measurements to within experimental uncertainty for 73% of ∆ G min estimates and 80% of SR min estimates. Computation time is seconds for initial E‐field maps and milliseconds for E‐field updates for different gradient designs, allowing for highly efficient iterative optimization of gradient designs and enabling new dimensions in PNS‐optimal gradient design. Conclusions: We have developed accurate and computationally efficient methods for prospectively determining PNS limits, with specific application to head gradient coils.